Science and technology in Kazakhstan: current status and future prospects - Amy Mour Mercer; Glenn Schweitzer (Foresight and STI Governance)
The article summarizes the results of an audit of scientific and technological activities in Kazakhstan. The study was conducted during 2006 by the US National Academy commissioned by the Ministry of Education and Science of Kazakhstan. The objective of the audit was to identify priority research and technology areas that deserve special government support in the next five years. Of course, the importance of these priorities is dependent on adequate science and technology policy, research capacity of public and private sectors, development of scientific and technical services of domestic and international markets for Kazakhstan's technology and quality human resources.